(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Carrizal Formation is one of the Triassic units of the Marayes - El Carrizal rift located in the eastern San Juan Province, Argentina (Figs. 1, 2). The facies analysis and the architectural study of the Carrizal Formation (Table 1) allowed recognising two facies associations. Facies association 1 corresponds to the Arroyo Seco Member (Fig. 3), and facies association 2 to the Rickard Member (Fig. 4). The Arroyo Seco Member (Figs. 3, 5) comprises vertical stacked channel belt conglomerates, associated with sandstones, gravelly sandstones and scarce mudrocks. Channel belt conglomerates are composed of extraformational rounded to subangular pebbles of gneiss, migmatite, schist, granitoid, anphibolite and quartz derived from the local crystalline basement. These deposits are encased in amalgamated lenticular beds composed of sandstones, gravelly sandstones and fine-grained conglomerates, in which trough cross-bedding is the most conspicuous sedimentary structure (Fig. 6). Thin and laterally continuous fine- and medium-grained sandstones and mudstones are less common. A monotypic corystospermaceae forest with 38 stems resting in live position was identified in one of the basal levels of the Arroyo Seco Member (Fig. 6). The deposits of this facies association are essentially the result of bedload accumulation in a braided fluvial system (cf. Smith, 1970; Miall, 1978; Bluck, 1979; Steel and Thompson, 1983; Ramos et al., 1986; Smith, 1990; Bristow and Best, 1993; Bristow, 1993b), characterised by marked changes in discharge and sediment supply. The Rickard Member (Fig. 4) consists of discrete conglomerate channel fill deposits cut into laterally extensive tabular deposits (sandstones, heterolithic intervals, mudstones, coal beds). Three sub-associations are recognised. The first sub-association is composed of discrete thick and lenticular conglomerate beds showing a well defined imbrication structure, and composed of subangular to rounded pebbles and cobbles derived from the local metamorphic-igneous basement (Fig. 7). The second sub-association consists of massive, trough and low-angle cross-bedded, medium- to coarse-grained sandstones and granule sandstones. Remains of reworked stems, very abundant in some levels, were identified in both sub-associations (Fig. 7). The stems in one of the most conspicuous levels are oriented in a NE-SW direction (Fig. 8). The third sub-association is characterised by tabular and laterally extensive massive, laminated and rippled beds of fine- to medium-grained sandstones (Fig. 7), heterolithic intervals, greenish to dark (carbonaceous) mudstones, and thin coal beds. Bioturbation is common (Fig. 7), and several fossiliferous beds composed of Cladophlebis sp., Dicroidium sp., Yabeiella sp., Kurtziana sp. and Johnstonia sp. have been identified in this sub-association. The deposits of the Rickard Member indicate a mixed-load fluvial system (Collinson, 1986; Spalletti and Barrio, 1998; Spalletti, 2001b) characterised by isolated channels encased in rapidly aggrading and extensive floodplains (Smith et al., 1989; Jensen and Pedersen, 2010). The Carrizal Formation shows a drastic change in the evolution of fluvial architecture (Fig. 9). The lower Arroyo Seco Member is dominated by tractional coarse-grained multistorey deposits, formed in gravelly and sandy alluvial plains with a discrete degree of incision. Instead, the upper Rickard Member was originated in a mixed load fluvial system, characterised by rapidly aggrading floodplain deposits in which the main channels are confined by sharp erosional bases and side banks. The vertical transition from bedload to mixed- load fluvial systems upwards suggests a marked change in the rate of creation of accommodation (McLaurin and Steel, 2007; Leleu et al., 2010). The Arroyo Seco Member is thus characterised as a low-accommodation systems tract and the Rickard Member as a high-accommodation systems tract (Fig. 9). The contact between these two members is a chronostratigraphic retrogradational surface which can be traced for several kilometres along strike.